Persistence of serum bactericidal antibody one year after a booster dose of either a glycoconjugate or a plain polysaccharide vaccine against serogroup C neisseria meningitidis given to adolescents previously immunized with a glycoconjugate vaccine - De Whalley, P; Snape, MD; Kelly, D; Banner, C; Lewis, S; Diggle, L; John, T; Yu, L; Omar, O; Borkowski, A; Pollard, A (2011)
Background: Bactericidal antibody induced by immunization of infants with serogroup C Neisseria meningitidis (MenC) vaccines wanes rapidly during childhood. Adolescents are at particular risk from meningococcal disease, therefore they might benefit from a booster dose of vaccine. The duration of serologic response to such a booster in adolescents is unknown. Methods: In a previous study, English schoolchildren, aged 9 to 12 years, who had received a monovalent MenC glycoconjugate vaccine in 1999-2000, were given either a plain polysaccharide vaccine (MenC-PS group, n = 150) or a glycoconjugate vaccine (MenC-CRM group, n = 95) at 13 to 15 years of age. In this follow-up study, serum bactericidal antibody titers and specific immunoglobulin G concentrations were assessed 1 year later. Results were compared with unboosted controls of similar age (control group, n = 298). Results: Compliance with study protocol was achieved for 146 of the MenC-PS group, 92 of the MenC-CRM group, and 293 of the control group. Compared with the control group, both the MenC-PS and MenC-CRM groups had a significantly higher (P < 0.0001) geometric mean serum bactericidal antibody titers 1 year after the booster dose (geometric mean titers for MenC-PS group 3388 [95% confidence interval CI: 2460-4665]; MenC-CRM group 4417 [95% CI: 2951-6609]; control group 316 [95% CI: 252-396]). Specific immunoglobulin G concentration also rose and remained elevated 1 year after the booster. Conclusions: A booster dose of MenC vaccine given to adolescents produced a marked rise in bactericidal antibody, which remained elevated 1 year later. Introduction of an adolescent booster of MenC vaccine might provide enhanced long-term population control of the disease. © 2011 by Lippincott Williams and Wilkins.